2017
DOI: 10.1111/boc.201600078
|View full text |Cite
|
Sign up to set email alerts
|

Are cancer cells really softer than normal cells?

Abstract: Solid tumours are often first diagnosed by palpation, suggesting that the tumour is more rigid than its surrounding environment. Paradoxically, individual cancer cells appear to be softer than their healthy counterparts. In this review, we first list the physiological reasons indicating that cancer cells may be more deformable than normal cells. Next, we describe the biophysical tools that have been developed in recent years to characterise and model cancer cell mechanics. By reviewing the experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
259
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(272 citation statements)
references
References 186 publications
(309 reference statements)
13
259
0
Order By: Relevance
“…Investigating the relation between cell biomechanics and human abnormalities has garnered much interest in recent years. 3,7 Young's modulus of highly invasive breast cancer cells was reported significantly lower than noninvasive breast cancer cells. Previous studies show that cancer cells express different mechanical and physical properties compared to healthy cells.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Investigating the relation between cell biomechanics and human abnormalities has garnered much interest in recent years. 3,7 Young's modulus of highly invasive breast cancer cells was reported significantly lower than noninvasive breast cancer cells. Previous studies show that cancer cells express different mechanical and physical properties compared to healthy cells.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 There are several studies that have demonstrated softening of cancerous cells such that mechanical properties of cancer cells correlate to their invasiveness. 3,7 Young's modulus of highly invasive breast cancer cells was reported significantly lower than noninvasive breast cancer cells. 8 These findings suggest that cellular mechanics strongly correlates with the cancer invasiveness, and Young's modulus might be an indicator of cancer cell invasiveness.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the stiffness of a tumour can be up to twenty fold higher than that corresponding to normal tissues [Baker et al., ; Egeblad et al., ; Tung et al., ]. Although these tumour tissues are more rigid, individual cancer cells are often softer than healthy cells [Alibert et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanics of cells could thus potentially be used as novel diagnostic and/or prognostic physical biomarkers to complement traditional histological examinations and genetic phenotyping [153]. However, in order to apply AFM single-cell mechanical assay in practical biomedical applications (e.g., cancer diagnosis), several issues need to be addressed.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…For clinical applications, the reliability of cell mechanic detection should be validated on many clinical cases. The procedures of clinical sample preparation and AFM measurements need to be standardized and the related value ranges of cancer cells and normal cells need to be confirmed [153]. Several studies have explored directly measuring the mechanics of primary tumor tissues and showed that tissue mechanics could indicate different stages during tumor metastasis [127], [128].…”
Section: Discussion and Perspectivementioning
confidence: 99%